REPRESENTASI LINGKUNGAN DALAM NOVEL KEMARAU DI SEDANAU KARYA ASRORUDDIN ZOECHNI MELALUI KAJIAN EKOKRITIK - Juliyan Dini, Viona; Shanty, Isnaini Leo; Habiba, Siti; Malik, Abdul; Irawan, Dody; Musliha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the representation of the environment in the novel Kemarau di Sedanau by Asroruddin Zoechni through an ecocritical perspective. The research was conducted based on the increasing importance of ecological awareness reflected in literary works as a response to environmental issues. The objective of this study is to describe the forms of environmental representation portrayed in the novel using the principles of literary ecology. This research employed a descriptive qualitative method. The researcher served as the primary research instrument, supported by data analysis guidelines. The data consisted of words, phrases, and sentences taken from the novel, collected through the note-taking technique and analyzed using content analysis. The findings reveal that environmental representation in the novel is reflected in four major aspects of literary ecology: respect for nature, responsibility toward nature, love and care for nature, and the principle of not harming nature. The novel portrays admiration and gratitude for nature, emphasizes human responsibility in preserving environmental balance, presents nature as an essential element that contributes to human comfort and harmony, and promotes ecological awareness through the wise and sustainable use of natural resources. These findings demonstrate that the novel not only functions as a literary work but also serves as a medium for fostering ecological values and environmental awareness among readers.